The Effectiveness Of Stream-ar-cc In Reducing Misconceptions On Climate Change, Improving Systems Thinking Skills And Relevance Among Form Two Students - Khan, Nur Sabrina Mohamed Ali (2023)
Climate change is a complex issue that has drawn significant attention from the government and society; and is a paramount educational concern in Malaysia. A well-structured and relevant climate change instruction can facilitate students’ ability to comprehend the knowledge of climate science, visualize the abstract concept and develop future capabilities to solve climate change problems. This interventional mixed-method study was aimed at developing an effective climate change instruction based on current practices. The first stage of the study explored the current practices of teaching and learning climate change in the ecosystem topic among secondary school students and teachers. The qualitative findings of the exploration informed the development of climate change instruction in stage two. The amalgamation of Science, Technology, reading and writing, Engineering, arts, and Mathematics (STrEaM) and AR (augmented reality) mobile application give rise to STrEaM-AR-CC teaching and learning approach. In the third stage, the effectiveness of STrEaM-AR-CC on the misconceptions of climate change, systems thinking skills and the relevance of science education among form two students were measured. A quasi-experimental, non-equivalent, pre- and post-test control group design was executed. A sample of 122 Form Two students from two secondary schools in Penang was randomly assigned as control and experimental groups. Interviews were conducted on the students from the experimental group before and after the execution of the STrEaM-AR-CC to gauge insight into the quantitative findings